The Historical and Endogenous Logic of Social Stability in China - Yanjie Yang (Studies in Social Science & Humanities, 2023)
The Chinese civilization has lasted for more than 5, 000 years, which has formed the cultural phenomenon of social stability in China. The reason of this stability can be traced back to the stress countermeasures of the primitive population to the natural and social environment, as a result, a meme is formed that causes are inherited by causes. China’s social stability has formed a systematic and complex dynamic self-consistent mechanism, and in the new historical period, with its unique charm coruscates the vigorous vitality.